Perception of Mathematics Self-Efficacy and Its Role in Academic Achievement: A Systematic Review - Dahal, Prem Prasad; G. C., Laxmi (Mathematics Education Forum Chitwan, 2025)
Mathematics self-efficacy (MSE) is an important non-cognitive factor that affects the student's achievement, motivation, and persistence in learning mathematics. It is a systematic review of twelve peer-reviewed journals, which were published between 2019 and 2025 and focus on the association between MSE and student achievement in various settings. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR, 2020) framework, the empirical and review studies on mathematics self-efficacy and achievement and their associated mediators or moderators were identified through electronic searches in Scopus, Web of Science, ERIC, SpringerLink, and Google Scholar. The evidence is consistent that higher MSE is correlated with an increase in confidence, persistence and academic success. The synthesis yielded five themes that are interrelated and that summarize the influence of MSE on achievement. First, issues of measurement indicate the importance of task-specific and multidimensional instruments for validity. Second, longitudinal studies imply a two-way street, with previous achievement usually predicting later self-efficacy. Third, efficacy and performance could be reinforced in the targeted interventions, including the mastery-oriented instruction, supportive pedagogy, and visualization tools such as GeoGebra that are dynamic. Fourth, the link between MSE and achievement is influenced by mediating and moderating factors such as cognitive ability, interest, anxiety, gender and socioeconomic background. Lastly, cross-cultural data of such countries as United States, Japan, Oman, Turkey and Nigeria confirm the applicability of MSE across the board and highlight contextual differences. The review concludes that the development of mathematics self-efficacy is a good and equitable way to improve achievement and decrease systemic disparities.